Transient Optical Properties of CsPbX3/Poly(maleic anhydride‐alt‐1‐octadecene) Perovskite Quantum Dots for White Light‐Emitting Diodes. Issue 1 (10th December 2020) - Xu, Jian; Zhu, Liang; Chen, Jia; Riaz, Saba; Sun, Liwei; Wang, Ying; Wang, Wei; Dai, Jun
Abstract : Poly(maleic anhydride‐ alt ‐1‐octadecene) (PMAO)‐coated green CsPbBr3 and red CsPbBr0.6 I2.4 quantum dots (QDs), as the phosphor materials for white light‐emitting diodes (WLEDs), are reported. The anhydride groups of PMAO can be bound to the surface ligands of perovskite QDs and act as a protective layer. The results show that CsPbX3 /PMAO (X = Cl, Br, I) presents good crystallinity and excellent luminescence properties. Time‐resolved photoluminescence (TRPL) shows that the PL lifetime of CsPbX3 /PMAO is prolonged, and the transient absorption (TA) results show that intraband hot‐exciton relaxation and exciton recombination can be slowed down when the CsPbX3 QDs are coated with PMAO. However, the PL quantum yields (PLQYs) increase for both the green‐emitting QDs and the red‐emitting QDs after PMAO coating. WLED devices are fabricated by integrating the green CsPbBr3 /PMAO QDs and red CsPbBr0.6 I2.4 /PMAO QDs on the blue GaN chips. The devices show stable white light emission with Commission Internationale de L'Eclairage (CIE) color coordinates of (0.314, 0.291). The results indicate that CsPbX3 /PMAO QDs can be an ideal downconversion fluorescent material for WLED devices. Abstract : The anhydride groups of poly(maleic anhydride‐ alt ‐1‐octadecene) (PMAO) can be bound to the surface ligands of perovskite quantum dots (QDs) and act as a protective layer. Furthermore, time‐resolved photoluminescence and ultrafast transient absorption spectroscopy reveal that the PMAO contributes to passivating the surface defects of the perovskite QDs.